Mawlānā Muhammad Āsif Qāsmī Scientific approach in his Tafsīr "Baṣīrat-e-Quran": A Descriptive Study - Dr. Muhammad Saeed; Dr. Amjad Hayat (Journal of Religion and Society, 2025)
Tafsīr "Baṣīrat-e-Quran" is a contemporary Tafsīr written by Mawlānā Muhammad Āsif Qāsmī, the grandson of Mawlānā Muhammad Qasim Nanotavi, the founder of Darul Uloom Deoband, India. Mawlānā Āsif Qāsmī is the author of several books. One of his books is his Tafsīr, "Baṣīrat-e-Quran," published in simple Urdu in 6 volumes in 2005. In his Tafsīr, he focuses on scientific issues and mentions his viewpoint in this regard. To know what the worth of the scientific discussion of this Tafsīr is and what his methodology is? This article will answer this research question. He discusses several scientific points, such as Scientist and Islam, The modern development of science, Discipline and organization of the universe, Honey Bee and her system, Skin speech, Fingerprints, Mixed Sperm, Ozone Layer, The world's rotation around the sun and its speed, Audio and Video calls and their possibility, The Dead Sea. In this article, I will analyse critically the scientific discussion of this Tafsīr. This research study aims to determine the worth of Tafsīr "Baṣīrat-e-Quran" from its scientific perspective. The methodology of this research is critical analysis. Keywords: Scientific Approach, Tafsīr "Baṣīrat-e-Quran", Āsif Qāsmī, Descriptive Analysis